Age-related Features of Bone Mineral Density Changes in Girls of Donetsk Region - F.V. Klymovytsky; Povoroznyuk V.V; N.N. Balatska (Zaslavsky O.Yu., 2012)
By using of dual-energy densitomet0er Discovery QPR (Bedford, USA) there was carried out an examination of 89 girls from one of secondary schools in Donetsk. Body build indices (fat mass, fat free mass and percentage of fat mass), body mass index were examined, as well as BMDWH, BMDLS, BMDFB. While studying BMD of the whole skeleton, lumbar spine and proximal left femur there was noted the growth of this index with increase of girls' age. It is found that with age the indices of children's body build grow progressively, particularly indices of fat free and fat mass. Thus these changes have reliable dependence on the age of girls. The age significantly influences the variability of bone mineral density indices and body build for the girls of different age. The features of body build changes in examined children were characterized by the fact that 14-15-year-old girls have significantly high indices of fat mass (p < 0.001) and in 13-16-year-old girls - percent of fat mass (p < 0.01-0.001).